(untitled) (Global Journal of Science Frontier Research, 2017)
The investigation of length-weight relationship, condition factor and some growth parameters of the black tiger shrimp (Penaeus monodon) were carried out in a monthly sampling over a period of twelve months in Andoni river system. The length-weight relationship of the shrimp was estimated using linear regression, a technique incorporated in the FAO-ICLARM Stock Assessment Tool (FiSAT). The condition factor of the shrimp was estimated from Fulton Condition factor (K) while age & growth structure of the shrimps were estimated using the modified Peterson method also known as the integrated method. The length-weight relationship showed a negative allometric growth pattern with values ranging from 1.4604 ± 0.0828 to 1.2999±0.0692 while Condition factor (K) varied from 0.5914 to 0.6909. The age or longevity of the oldest tiger shrimp was 3.448 years. Asymptotic length (L∞) and growth coefficient (K) were 31.5cm and 0.870yr-1 respectively. The length at first capture Lc was 12.44cm. The growth performance index ( ) was 2.936.